Sulfur-Responsive Elements in the 3′-Nontranscribed Intergenic Region Are Essential for the Induction of SULFATE TRANSPORTER 2;1 Gene Expression in Arabidopsis Roots under Sulfur Deficiency. Issue 4 (8th April 2015) - Maruyama-Nakashita, Akiko; Watanabe-Takahashi, Akiko; Inoue, Eri; Yamaya, Tomoyuki; Saito, Kazuki; Takahashi, Hideki
Abstract : Root-to-shoot transportation of the essential nutrient sulfate requires a unique molecular mechanism that controls the expression of a sulfate transporter in root vascular tissues. Abstract: Under sulfur deficiency (−S), plants induce expression of the sulfate transport systems in roots to increase uptake and root-to-shoot transport of sulfate. The low-affinity sulfate transporter SULTR2;1 is predominantly expressed in xylem parenchyma and pericycle cells in Arabidopsis thaliana roots under –S. The mechanisms underlying –S-inducible expression of SULTR2;1 in roots have remained unclear, despite the possible significance of SULTR2;1 for acclimation to low-sulfur conditions. In this investigation, examination of deletions and base substitutions in the 3′-intergenic region of SULTR2;1 revealed novel sulfur-responsive elements, SURE21A (5′-CAATGTATC-3′) and SURE21B (5′-CTAGTAC-3′), located downstream of the SULTR2;1 3′-untranslated region. SURE21A and SULTR21B effectively induced reporter gene expression from fusion constructs under –S in combination with minimal promoters or promoters not inducible by –S, suggesting their versatility in controlling transcription. T-DNA insertions near SURE21A and SULTR21B abolished −S-inducible expression of SULTR2;1 in roots and reduced the uptake and root-to-shoot transport of sulfate. In addition, these mutations partially suppressed SULTR2;1 expression in shoots, without changing its –S-responsive expression. These findings indicate that SULTR2;1 contributes to the increase in uptake and internal translocation of sulfate driven by gene expression induced under the control of sulfur-responsive elements in the 3′-nontranscribed intergenic region of SULTR2;1 .